COVID-19 Positive Neonates from Pregnant Women with COVID-19 in Kasih Ibu Hospital Surakarta - Nabila Arnest Amorita; Mas Nugroho Ardi Santoso (MBUnivPress, 2021)
Kasih Ibu Hospital from October 2019 to January 2021 has become the referral maternal COVID-19 hospital in Surakarta, Central Java. Until now, research on pregnant women with COVID-19 in Indonesia is still very limited, it is still unknown whether there are possibility of vertical transmission from mother to baby, while pregnant women are among the vulnerable population. The purpose of this study is to provide an overview of the findings of positive infant outcomes for COVID-19 in pregnant women with confirmed COVID-19 at Kasih Ibu Hospital, Surakarta. Data collection was carried out by tracing medical records which were then presented in the form of distributions based on gestational age, infant birth weight, infant APGAR score, and infant COVID-19 status. Out of 62 pregnant women confirmed positive for COVID-19, 20 babies (32.3%) had PCR swab tests positive for COVID-19. All babies were born in good shape (APGAR score 8-10) and 4 babies were found with low birth weight, one of whom also had hypospadias. There were no reports of neonatal asphyxia and infant mortality.